Early use of erenumab in US real-world practice. (24th May 2021) - Bogdanov, Alina; Chia, Victoria; Bensink, Mark; Urman, Robert; Fischer, Lauren; Rasmussen, Soeren; Szekely, Christine; Kallenbach, Lee
Background: Erenumab, a monoclonal antibody (mAb) developed to block the calcitonin gene-related peptide (CGRP) receptor, is approved for the prevention of migraine in adults. This retrospective observational study sought to describe early real-world use of erenumab. Methods: This study used the Practice Fusion ambulatory Electronic Health Record database, which represents approximately 6% of ambulatory care among primary care and specialist practices in the United States. Among migraine patients initiating erenumab, demographics, migraine type, comorbidities, and prior treatments were assessed during the 12-month baseline period. Treatment patterns including changes in acute and preventive medications, switches to other CGRP mAbs (fremanezumab and galcanezumab), and for erenumab, changes in dose and adherence were examined among patients with 6 months of follow-up. Results: Of 3, 336 patients identified (85.9% female; mean age = 49.1 years), approximately 40% had documentation of chronic migraine. Common comorbidities included non-migraine headache, anxiety, depression, and hypertension. Most patients (76.3%) initiated on the 70 mg dose of erenumab. Among 1, 638 patients included in the treatment pattern analysis, 53.1% used acute medications and 55.7% used other non-specific preventive migraine medications during follow-up, reductions of 9.8% and 10.2%, respectively, over the same period of time before index. Switching to fremanezumab and galcanezumab were observed in 12.2% and 13.8% of patients, respectively. The mean proportion of days covered by erenumab at 6 months was 79%. Dosage of erenumab increased (from 70 mg to 140 mg) in 13.0% and decreased (from 140 mg to 70 mg) in 24.9% of patients. Conclusion: This early real-world study showed high adherence among erenumab users. This combined with observed reductions in previously used acute and preventive medications are suggestive of erenumab's benefit.